Spondias mombin Ameliorates Copper-Induced Memory Impairment in Mice by Mitigating Oxidative Stress and Modulating Cholinergic Activity - James Busayo Agboola; Amos Rotimi Joshua; Sanmi Tunde Ogunsanya; Adeola Folashade Ehigie; Janet Olufumilayo Oke; Omodesola Oluwafisayo Ogunruku (Journal of Toxicology)
The study unveils the importance of Spondias mombin leaf extract (S. mombin: 100 mg/kg b.wt.) in mitigating the toxic insult mediated by copper (16 mg/kg) on the cholinergic system via oral gavage. Male mice were weighed and distributed into five groups, six mice per group. Group A represents the basal control group given only distilled water; Group B and C were given 16 mg/kg of copper sulphate and 100 mg/kg of S. mombin methanol leaf extract, respectively, for 31 days; Group D was given 16 mg/kg of copper sulphate for 31 days, followed by treatment with 100 mg/kg of S. mombin methanol leaf extract for 15 days; and Group E was assigned only S. mombin. The copper concentration was evaluated using atomic absorption spectroscopy, while the cognitive abilities were assessed using Morris water maze and elevated plus-maze. The result showed that S. mombin reversed the disparities in cholinesterase and choline acetyltransferase activities in vivo due to copper neurotoxicity, with a relative (p<0.05) decrease in brain and blood copper concentration in co- and posttreatment groups. Furthermore, S. mombin reported decreased the disparity between pro- and antioxidant occurrence caused by copper toxicity by lowering brain lipid peroxidation, raising thiol levels, and increasing the activities of antioxidant enzymes such as glutathione transferase, catalase, and superoxide dismutase. The result showed that the extract had a protective influence on memory deficits (p<0.05), significantly reduced anxiety levels, and increased the overall number of neurons in the hippocampus subfields. In conclusion, S. mombin ameliorates Cu-induced neurotoxicity and neurocognitive dysfunctions by virtue of enhancement of cholinergic signalling and antioxidant activities in the brain.